CD10-Positive Cutaneous PEComa: An Extremely Rare Skin Tumour - Simon Ueberschaar; Matthias Goebeler; Hermann Kneitz (Karger Publishers, 2020)
We here present the case of a 67-year-old woman with a history of a slowly progressive, polypous nodule on her left wrist. The lesion was excised, and the histological analysis revealed a clear cell tumour that was relatively sharply demarked from the surrounding tissue extending into the subcutaneous tissue. The tumour showed a characteristic trabecular pattern in which the tumour cells were arranged around numerous vessels. The neoplastic cells had a predominantly epithelioid shape, granular eosinophilic to clear cytoplasm and prominent centrally located nucleoli. The histological differential diagnosis included a metastatic clear-cell renal cell carcinoma and a primary cutaneous perivascular epithelioid cell tumour (PEComa). Immunohistochemically, the tumour cells revealed homogenous expression of HMB-45, MiTF and CD10, whereas MART-1 and S100 were negative. Antibodies against actin marked the trabecularly arranged vessels, and the neoplastic cells yielded a patchy positivity against actin and desmin. Additional immunohistochemical stains against pan-cytokeratin, CAIX, PAX-8 and EMA were negative. Based on the morphologic and immunophenotypic findings, the histological diagnosis of a CD10-positive cutaneous PEComa was made.